2015
DOI: 10.2965/jwet.2015.249
|View full text |Cite
|
Sign up to set email alerts
|

Sediment-Associated Radiocesium Originated from Fukushima Daiichi Nuclear Power Plant Flowing from Ohori River to Lake Teganuma

Abstract: Radiocesium has been deposited after the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident and affix to the soils inland. The soils flowed into Lake Teganuma through Ohori River. Field observation was carried out to quantify radiocesium, associated with sediments, transported around Lake Teganuma and Ohori River from October 2011 to March 2014. We quantified the sediment transported to Ohori River and found that the total radiocesium stock in Ohori River was 2,190 MBq which was mostly attached to the fine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…These annual loss rates are larger than those reported for other land uses on hillslopes (0.0029% −12%) [19,27] and for catchments (0.4%−1.4%) [22], even without human activities in the evacuation zone. This rapid removal of 137 Cs from urban areas is also consistent with larger wash-off from urbanized catchments compared with other land uses reported by studies of Cs in river systems [22,54,55]. These studies indicate that the recovery in urban areas from radiocesium contamination is faster than in other terrestrial environments.…”
Section: Recovery From 137 Cs Contamination In Urban Areassupporting
confidence: 84%
“…These annual loss rates are larger than those reported for other land uses on hillslopes (0.0029% −12%) [19,27] and for catchments (0.4%−1.4%) [22], even without human activities in the evacuation zone. This rapid removal of 137 Cs from urban areas is also consistent with larger wash-off from urbanized catchments compared with other land uses reported by studies of Cs in river systems [22,54,55]. These studies indicate that the recovery in urban areas from radiocesium contamination is faster than in other terrestrial environments.…”
Section: Recovery From 137 Cs Contamination In Urban Areassupporting
confidence: 84%
“…The likely main contributors to the declining trend include (a) hydraulic ushing out of sediments and (b) downward migration of radiocesium through sedimentation and diffusion-advection. Hydraulic ushing may strongly affect shallow ponds (for example P1, P3 and P4) because they can be easily agitated by strong winds, 17,43 heavy rains and typhoons; 15 and ponds of large catchment-to-surface-area ratios which yield low radiocesium trap efficiency 21 so that radiocesium-rich ne sediments are ushed out. Yoshimura et al 44 observed such hydraulic ushing in some Fukushima ponds of low trap efficiency.…”
Section: Temporal Changes In Radiocesium Concentrationmentioning
confidence: 99%
“…The results suggest that the FDM prediction will lead to a longer period of contamination with low-level 137 Cs than the TDM prediction.During the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident, aquatic ecosystems are contaminated with radioactive 137 Cs 1-6 . At present, the activity concentration of 137 Cs in river water is quite low [7][8][9] . However, in closed lakes, there is a problem of long-tailed temporal change in low-level radioactive contamination because the activity concentration declines steeply immediately after the accident, but then turns to a gradual decrease 6,10 .…”
mentioning
confidence: 96%